Enriching Immersive Learning Experience During Movement Control Order (MCO) Through Blended Learning Substitution Method - Afzan, Ahmad Zaini (UNIMAS Publisher, 2023)
Blended or hybrid learning is a self-directed learning, project-based learning and remote learning that combines both online and face-toface learning. It allows online educational materials and opportunities for online interaction with traditional classroom methods. Blended learning requires the physical presence of both teacher and student, with some elements of student control over time, place and direction. Hybrid education uses online technology to not just supplement but transform and improve the learning process. This course (BEQ 1073 Construction Economics for Quantity Surveyors I) adopted Blended Learning Substitution which was introduced by Malaysian Qualifications Agency (MQA) and the university due to Movement Control Order (MCO) on 18th March 2020. Several platforms were used to implement Blended Learning Substitution method for this course such as eLEAP, live classroom, forum, and simulations based on the real construction project. A new course plan was developed using asynchronous mode for the remaining half of the semester to enable students with poor internet connection to get access.